Students’ Perception of Edmodo use as a Learning Tool - Siahaan, Erna Basania (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2020)
Due to the development of technology, teachers are expected to integrate technology into the classroom to engage the Z Generation students. Edmodo is a popular online learning platform that has now been widely used as a learning management system in blended learning or just as a supplementary tool. This study aims at investigating students' perceptions of Edmodo as a learning tool. Involving 47 students of the English department of Universitas Kristen Indonesia, data were collected employing a questionnaire and an interview. The results showed that the participants perceived Edmodo use improved their language skills, developed interaction and communication, enhanced the freedom to share ideas, and promoted their vocabulary and creativity. However, they regarded that the traditional face-to-face learning should not be replaced by online learning. They seemed to suggest the two learning modes combined.